International Study of Student Career Choice in Psychiatry (ISoSCCiP): Results from Modena, Italy. (August 2013) - Ferrari, Silvia; Reggianini, Corinna; Mattei, Giorgio; Rigatelli, Marco; Pingani, Luca; Bhugra, Dinesh
Abstract Italy was one of the 16 countries to take part in the International Study of Student Career Choice in Psychiatry (ISoSCCiP). This paper reports and comments on the IsoSCCiP data on Italian medical students. Italian final year medical students from the University of Modena and Reggio Emilia were asked to fill in an on-line questionnaire during the first semester of two consecutive academic years (2009–2010, 2010–2011). Step-wise logistic regressions were performed. Of the 231 students invited, 106 returned completed questionnaires (response rate = 46.7%). Women constituted 66%, and mean age was 25.14 (SD = 1.15). Psychiatry was the second most common choice of possible career by students (5.7%, n = 6). Choosing psychiatry was predicted by having volunteered for further clinical/research activities in psychiatry (p = 0.01), believing that 'the problems presented by psychiatric patients are often particularly interesting and challenging' (p < 0.01), and by accounts of personal/family experience with physical illness (p < 0.01). Both personal factors and factors related to training may be involved in the choice of psychiatry among Italian medical students. Cultural and organizational specificities of Italian mental healthcare may be involved, particularly the strong tradition of social psychiatry.